Pengaruh Jerami Padi dan Bokashi Jerami Padi Terhadap Sifat Kimia di Lahan Pasang Surut - Umie Shorayah; Ahmad Kurnain; Muhammad Indar Pramudi (Universitas Lambung Mangkurat, 2022)
Most farmers in tidal swamp areas optimized their land by using inorganic and organic fertilizers. The inorganic fertilizer has limited to get while many organic matter resources such as water hyacinth, Azolla, Kayapu, crop waste (straw), and rice husks widely available. This local potential supported the adoption of sustainable organic farming systems on tidal lands, particularly in South Kalimantan. The utilization of straw can be applied directly to the soil or made into bokashi. Therefore, an experiment of rice straw and bokashi of rice straw application to restore the fertility in the tidal swamplands had been conducting. This study used a completely randomized design method (CRD) with a single factor with five treatments: control, rice straw 2.5 and 7.5 tons ha-1 bokashi 2.5 and 7.5 tons ha-1. Each treatment had been repeating four times. The results showed that the application of bokashi of rice straw could increase soil pH, N-ammonium, and N-nitrate in the soil. On the other side, the application of fresh rice straw could reduce the soil's N-ammonium and N-nitrate content